Venepuncture: the medicolegal hazards. - McConnell, A. A. (BMJ Group, 1996)
Venepuncture is commonly regarded as a trivial procedure allocated to the most junior medical staff. The result of this policy is that junior doctors are required to perform a minimally invasive procedure on consenting patients without any structured venepuncture training or assessment. Consequently, inexperienced doctors may perform multiple and sometimes unnecessary, venepunctures, which could damage essential venous access, eg, in the diabetic or renal patient. We review the medicolegal position and suggest that structured venepuncture training is essential and argue that unskilled treatment may be regarded by the Courts as demonstrating the mens rea of assault in the form of recklessness.